2021
DOI: 10.31083/j.ejgo4205150
|View full text |Cite
|
Sign up to set email alerts
|

The role of microbiota in epithelial ovarian cancer: a scoping review

Abstract: The objective of this review was to examine the comprehensive role of microbiota in epithelial ovarian carcinogenesis. Methods: A scoping review method was used, and relevant databases were searched using combinations of key terms. Human and animal studies were selected that met inclusion criteria and critical appraisal tools were used to assess study quality. Results: A total of 10 international studies (human n = 8; animal n = 2) were included with total samples sizes varying from 16 to 580. Mean/median ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 95 publications
(173 reference statements)
0
1
0
Order By: Relevance
“…Intestinal microecology is a dynamic ecosystem influenced by gut microbial diversity and composition and is closely associated with immune responses and different disease. 10,11 Numerous studies have reported that gut microbiota is a potential target for regulating allergic asthma, AD, and other immune-related diseases. 12 The gut and skin share several similar features, and the "gutskin" axis is considered as a novel target for preventing AD.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal microecology is a dynamic ecosystem influenced by gut microbial diversity and composition and is closely associated with immune responses and different disease. 10,11 Numerous studies have reported that gut microbiota is a potential target for regulating allergic asthma, AD, and other immune-related diseases. 12 The gut and skin share several similar features, and the "gutskin" axis is considered as a novel target for preventing AD.…”
Section: Introductionmentioning
confidence: 99%